An Analysis on Politeness Strategy in Learning Interaction through WhatsApp Group - Kholilah, Ni'matul (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
To succeed the interaction, the linguistic features used must be inserted with politeness. The impact of politeness affects various aspects in societies, especially in education of young generation, it can affect the way they communicate one another. In context learning, communication between students and teachers must be well formed and delivered. This research aimed to examine the kinds of politeness strategy and the strategy used to deliver the types of politeness strategy on learning interaction through WhatsApp group. The research used a descriptive qualitative method to describe, explain and analyze the kinds of politeness strategies and the strategies that used to deliver the types of politeness strategies based on theory of Brown and Levinson. The data of this research was conversation in the WhatsApp Group. The instrument of this research was the researcher herself. Furthermore, the method used to collect the data was documentation. From the analysis, the researcher found all kinds of politeness strategy that students used in online learning interaction through WhatsApp group. Those were positive politeness strategy, negative politeness strategy, bald-on record strategy, and off-record strategy. Moreover, students used most of the strategies to deliver the kinds of politeness strategy. In the positive politeness strategy there were 11 strategies that students used, there were 6 strategies used to deliver the negative politeness strategy, 3 strategies used to deliver bald-on record strategy, and 2 strategies used to deliver off-record politeness strategy.